The Effect of Fintech on the Financial Performance of Sharia Banking - Ita Udi Wijaya (JEKAMI Journal of Accounting, 2022)
This study aims to determine the effect of fintech on the financial performance of Islamic banking. This type of research used in this research is descriptive research with a quantitative approach. The population in this study is all financial reports that have been published by Islamic banks that have started using fintech, namely Bank BNI Syariah, Bank BRI Syariah, Bank Syariah Mandiri, Bank BCA Syariah, Bank Syariah Bukopin and Bank BJB Syariah for the period 2016-2018. Based on the purposive sampling method, the sample used in this study is Islamic Commercial Banks that have used fintech services such as Internet Banking, Mobile Banking, SMS banking, and Phone Banking and publish annual financial reports from time to time during the study period, namely from 2016. -2018. Data management uses SPSS 25. The results prove that fintech has an effect on financial performance (ROA, ROE, BOPO, CAR, FDR). The more fintech services develop in Islamic finance, the more they have a significant effect on the financial performance of Islamic banking.